ElderCare Monitor Application Design: Elderly Health Monitoring based on Family and Community Health Center Collaboration - Wa Ode Tanti; Sri Kusumadewi; Rahadian Kurniawan (JUITA: Jurnal Informatika, 2025)
The elderly are a vulnerable group that is susceptible to various degenerative diseases. The lack of information and understanding of the elderly causes a high rate of disease complications. This study aims to design an ElderCare Monitor application that is easy to use and tailored to the needs of users. The application caters to a variety of users, including elderly families, the elderly themselves, the pre-elderly, and health center officers. Health workers at the health center and the elderly's family collaborate to independently monitor the health of the elderly and pre-elderly. The system is designed using the design thinking method. The design thinking method involves five stages: empathy, define, ideate, prototyping, and testing. The results of the study showed an effectiveness rate of 95.24% for the elderly and families and 95.83% for health center officers. The average SUS score for families and the elderly was 74.17, while for medical personnel, it was 77.5. Therefore, the ElderCare application received the "Good" usability category. This study contains numerous components that may serve as encouragement. In particular, it is imperative that we consistently improve the UI/UX of ElderCare by routinely gathering user feedback and incorporating features that can more effectively support the elderly.